2017
DOI: 10.3389/fphar.2017.00673
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra chinensis Stem Ameliorates 3-Nitropropionic Acid-Induced Striatal Toxicity via Activation of the Nrf2 Pathway and Inhibition of the MAPKs and NF-κB Pathways

Abstract: The beneficial value of the stems of Schisandra chinensis (SSC) in neurological diseases is unclear. We examined whether SSC aqueous extract (SSCE) alleviates striatal toxicity in a 3-nitropropionic acid (3-NPA)-induced mouse model of Huntington's disease (HD). SSCE (75, 150, or 300 mg/kg/day, p.o.) was given daily before or after 3-NPA treatment. Pre- and onset-treatment with SSCE displayed a significant protective effect and pretreatment was more effective as assessed by neurological scores and survival rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…The intensification of oxidative processes in brain mitochondria was accompanied by the increase of GSSG content and decrease of GSH concentration as well as decrease of GSH/GSSG ratio, which were additional important indicators of oxidative stress and mitochondrial dysfunction [ 13 , 15 ]. Our findings were in concordance with previous studies where the disturbances in mitochondrial bioenergetics, defects in mitochondrial complexes II–IV, F 1 F 0 ATP-ase, and aconitase, mitochondrial swelling, disbalance in the pro-antioxidant system, excessive mitochondrial fission, and subsequent neuronal cell death in different regions of the brain after prolonged and acute 3-NPA treatment have been demonstrated [ 4 , 38 , 39 , 40 ]. Numerous pieces of evidence from clinical and experimental studies validated the key role of oxidative stress and concomitant mitochondrial dysfunction in mediating the neuronal degeneration and behavioral abnormalities at HD as well as after the exposure to neurotoxin 3-NPA [ 3 , 6 , 8 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The intensification of oxidative processes in brain mitochondria was accompanied by the increase of GSSG content and decrease of GSH concentration as well as decrease of GSH/GSSG ratio, which were additional important indicators of oxidative stress and mitochondrial dysfunction [ 13 , 15 ]. Our findings were in concordance with previous studies where the disturbances in mitochondrial bioenergetics, defects in mitochondrial complexes II–IV, F 1 F 0 ATP-ase, and aconitase, mitochondrial swelling, disbalance in the pro-antioxidant system, excessive mitochondrial fission, and subsequent neuronal cell death in different regions of the brain after prolonged and acute 3-NPA treatment have been demonstrated [ 4 , 38 , 39 , 40 ]. Numerous pieces of evidence from clinical and experimental studies validated the key role of oxidative stress and concomitant mitochondrial dysfunction in mediating the neuronal degeneration and behavioral abnormalities at HD as well as after the exposure to neurotoxin 3-NPA [ 3 , 6 , 8 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…We consider that in our case, Nrf2 activation with an accumulation of Nrf2 protein in the nucleus, can result from 3-NPA-induced ROS overproduction, especially O 2 •− , GSH/GSSG redox alteration, loss of ATP, or even as a direct response to SDH inhibition. Our findings coincide with previous reports that acute and prolonged 3-NPA administration provokes Nrf2 activation in neuronal cells [ 38 , 53 , 61 ] and this process was ROS-regulated [ 16 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Schisandrin is reported to restrain the cartilage degradation and inflammation by inhibiting the MAPK and NF-κB pathway [ 25 ]. Schisandrin reveals the anti-toxicity through the activation of the Nrf2 pathway and inhibition of MAPKs and NF-κB pathway [ 14 ]. In our study, the degradation of IκBα and the phosphorylation of IκBα and IKKα/β in STZ induced group were significantly reversed after schisandrin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Schisandrin is a natural active ingredient derived from the Chinese herb fruit, Schisandra chinensis [12]. Numerous studies have reported that schisandrin is beneficial for the central nervous system by inhibiting neuroinflammation [13], relieving endoplasmic reticulum stress [14], and suppressing autophagy [15]. Schisandrin is further reported to exert protective effects against glutamate-induced toxicity through inhibiting intrinsic mitochondria-dependent apoptosis, suggesting the implication of schisandrin in mitochondrial regulation [16].…”
Section: Introductionmentioning
confidence: 99%